Tyrosine kinase 2 promotes sepsis-associated lethality by facilitating production of interleukin-27. Issue 1 (6th March 2014) - Bosmann, Markus; Strobl, Birgit; Kichler, Nadia; Rigler, Doris; Grailer, Jamison J; Pache, Florence; Murray, Peter J; Müller, Mathias; Ward, Peter A
Abstract : Tyrosine kinase 2 is required for release of IL-27(p28) by TLR4-activated macrophages; disruption of this pathway is protective during in vivo models of sepsis. ABSTRACT: The aim of this study was to test the hypothesis that gene expression and release of IL-27 may be modulated by Tyk2. Macrophages derived from the peritoneum or bone marrow of C57BL/10SnJ (WT) mice produced abundant amounts of IL-27(p28) following TLR4 activation by LPS. In contrast, production of IL-27(p28), but not EBI3, was reduced by ∼50% in TLR4-activated macrophages derived from mice with genetic deficiency of Tyk2 compared with WT macrophages. Frequencies of IL-27(p28)+F4/80+CD11b+ cells were lower in TLR4-activated macrophages derived from Tyk2−/− mice. Mechanistically, Tyk2−/− resulted in disruption of a type I IFN-dependent mechanism for production of IL-27(p28), which was induced by type I IFNs, and release of IL-27 was defective in macrophages from IFN-β−/− and IFNAR1−/− mice. In contrast, Tyk2 was not required to mediate the effects of IL-27 on target gene expression in CD4 + T cells. In vivo, we observed that Tyk2−/− mice have improved survival following endotoxic shock or polymicrobial sepsis induced by CLP. Plasma levels of IL-27(p28) during endotoxic shock or polymicrobial sepsis were markedly reduced in Tyk2−/− mice compared with WT mice. Disruption of IL-27 signaling using IL-27RA−/− mice was protective against sepsis-associated mortality. These data suggest that Tyk2 may mediate adverse outcomes of SIRS by promoting the production of IL-27. In conclusion, this report identifies Tyk2 as a prerequisite factor in the molecular networks that are involved in generation of IL-27.